2014
DOI: 10.4102/curationis.v37i1.1148
|View full text |Cite
|
Sign up to set email alerts
|

Views of professional nurses regarding low tuberculosis cure rate in Greater Giyani Municipality, Limpopo Province

Abstract: The involvement of community stakeholders in TB prevention, health promotion and education activities devoted to disease spread and cure is vital so that the stigma attached to TB can be eliminated. TB education and awareness programmes should be included in the curriculum of primary schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Conclusively, a weak system for coordinating patient care can potentially lead to fewer patients appearing at the final evaluation. Similar challenge is also reported by Dong et al ,18 Edington and Hodkinson,19 and Maswanganyi et al 20. With change in reporting requirement by WHO, coupled with an inadequacy in programmatic efforts, the focus shifted from ‘cure’ to ‘treatment completed’, and final evaluations started to be under-rated.…”
Section: Discussionsupporting
confidence: 54%
“…Conclusively, a weak system for coordinating patient care can potentially lead to fewer patients appearing at the final evaluation. Similar challenge is also reported by Dong et al ,18 Edington and Hodkinson,19 and Maswanganyi et al 20. With change in reporting requirement by WHO, coupled with an inadequacy in programmatic efforts, the focus shifted from ‘cure’ to ‘treatment completed’, and final evaluations started to be under-rated.…”
Section: Discussionsupporting
confidence: 54%
“…Currently, this system is considered deficient by nurses, due to the way users are conducted. 17 Another point to consider is the nurses" knowledge regarding integrating programs, services, and health professionals. A study observed that, when referral to a specialized service occurs, there are no meetings to discuss cases, opposing the TB Control Program family and community.…”
Section: Ras Organization For Tbmentioning
confidence: 99%